Psychological Barriers in Science Education: Correlation of Science Anxiety and Academic Performance - Muslihah, Fitriyyatul; Rahmat, Adi; Winarno, Nanang (Unnes Science Education Journal, 2025)
Science anxiety is a debilitating combination of anxious negative emotion and cognition in the context of science education. This study investigates the relationship between students' science anxiety and their academic performance in science learning at the junior high school level. Employing a quantitative descriptive approach with a survey-based research design, the study gathered data from 109 students aged 12 to 15 years old. The Science Anxiety was used to assess students' levels of anxiety across personal and environmental dimensions. The survey result shown that science anxiety scale scale among junior high school students is 2.31, which both of them considered as low category. The findings reveal a moderate, negative correlation (r = -0.509, p < 0.001) between students' science anxiety and their learning outcomes. This inverse relationship suggests that as students' science anxiety increases, their academic performance tends to decrease. Conversely, lower levels of science anxiety are associated with better learning outcomes. The results highlight the significant impact of psychological factors, particularly anxiety, on students' engagement and achievement in science education.  Based on the students’ answers to open-ended questions, they are feel comfortable when learning science at school because of kind and friendly teacher. On the other hand, students who feel anxious in learning science when they found difficulties to comprehend scientific formulas. The findings provide valuable insights for educators and policymakers to develop targeted interventions and strategies that foster a more positive and inclusive science learning experience for all students.